2002
DOI: 10.1046/j.1440-1746.2002.02882.x
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit model of non‐cirrhotic portal fibrosis with repeated immunosensitization by rabbit splenic extract

Abstract: This animal model showed significant splenomegaly, with persistent rise in portal pressure without hepatic parenchymal injury, quite akin to NCPF seen in humans. This study also proposes that repeated immunostimulation may have an important role in the pathogenesis of NCPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…Recently, a rabbit model of NCPF has been developed by repeated injection of E. coli through an indwelling cannula into the gastrosplenic vein. These animals show marked portal hypertension with peripheral vasodilation and obtunded response to vasoactive agents [22]. This information further substantiates that in NCPF, a state of hyperdynamic circulation exists and all major circulatory beds, the splanchnic, cardiac, pulmonary and systemic are affected.…”
Section: Discussionsupporting
confidence: 72%
“…Recently, a rabbit model of NCPF has been developed by repeated injection of E. coli through an indwelling cannula into the gastrosplenic vein. These animals show marked portal hypertension with peripheral vasodilation and obtunded response to vasoactive agents [22]. This information further substantiates that in NCPF, a state of hyperdynamic circulation exists and all major circulatory beds, the splanchnic, cardiac, pulmonary and systemic are affected.…”
Section: Discussionsupporting
confidence: 72%
“…Repeated intramuscular injection of splenic extract was shown [51] to produce significant splenomegaly and rise in portal pressure at 1, 3, and 6 months without hepatic parenchymal injury, quite akin to NCPF seen in humans.…”
Section: Repeated Immunosensitization By Rabbit Splenic Extractmentioning
confidence: 93%
“…Idiopathic portal hypertension like changes in the liver and the development of portal hypertension have been reported after injecting dead non‐pathogenic colon bacilli into the portal vein of rabbits and dogs 18,19 . Recently in a model of indwelling cannulation of gastrosplenic vein, we showed that repeated injections of Escherichia coli resulted in development of splenomegaly and rise in portal pressure at 3 months 20 …”
Section: Etiopathogenesismentioning
confidence: 97%